Putting Structural Variants Into Practice: The Role of Chromosomal Inversions in the Management of Marine Environments - Nadja M. Schneller; Jan M. Strugnell; Matt A. Field; Kerstin Johannesson; Ira Cooke (Molecular Ecology, 2025)
Major threats to marine species and ecosystems include overfishing, invasive species, pollution and climate change. The changing climate not only imposes direct threats through the impacts of severe marine heatwaves, cyclones and ocean acidification but also complicates fisheries and invasive species management by driving species range shifts. The dynamic nature of these threats means that the future of our oceans will depend on the ability of species to adapt. This has led to calls for genetic interventions focussed on enhancing species' adaptive capacity, including translocations, restocking and selective breeding. Assessing the benefits and risks of such approaches requires an improved understanding of the genetic architecture of adaptive variation, not only in relation to climate‐resilient phenotypes but also locally adapted populations and the fitness of hybrids. Large structural genetic variants such as chromosomal inversions play an important role in local adaptation by linking multiple adaptive loci. Consequently, inversions are likely to be particularly important when managing for adaptive capacity. However, under some circumstances, they also accumulate deleterious mutations, potentially increasing the risk of inbreeding depression. Genetic management that takes account of these dual roles on fitness is likely to be more effective at ensuring population persistence. We summarise evolutionary factors influencing adaptive and deleterious variation of inversions, review inversions found in marine taxa, and provide a framework to predict the consequences of ignoring inversions in key management scenarios. We conclude by describing practical methods to bridge the gap between evolutionary theory and practical application of inversions in conservation.

Heterogeneity in choice models of addiction: the role of context - Samuel F. Acuff; Justin C. Strickland; Kirsten Smith; Matt Field (Psychopharmacology, 2024)

Chromosomal inversions harbour excess mutational load in the coral, Acropora kenti , on the Great Barrier Reef - Jia Zhang; Nadja M. Schneller; Matt A. Field; Cheong Xin Chan; David J. Miller; Jan M. Strugnell; Cynthia Riginos; Line Bay; Ira Cooke (Molecular Ecology, 2024)
The future survival of coral reefs in the Anthropocene depends on the capacity of corals to adapt as oceans warm and extreme weather events become more frequent. Targeted interventions designed to assist evolutionary processes in corals require a comprehensive understanding of the distribution and structure of standing variation, however, efforts to map genomic variation in corals have so far focussed almost exclusively on SNPs, overlooking structural variants that have been shown to drive adaptive processes in other taxa. Here, we show that the reef‐building coral, Acropora kenti , harbours at least five large, highly polymorphic structural variants, all of which exhibit signatures of strongly suppressed recombination in heterokaryotypes, a feature commonly associated with chromosomal inversions. Based on their high minor allele frequency, uniform distribution across habitats and elevated genetic load, we propose that these inversions in A . kenti are likely to be under balancing selection. An excess of SNPs with high impact on protein‐coding genes within these loci elevates their importance both as potential targets for adaptive selection and as contributors to genetic decline if coral populations become fragmented or inbred in future.

Consistent patterns of fungal communities within ant-plants across a large geographic range strongly suggest a multipartite mutualism - Melinda J. Greenfield; Lori Lach; Brad C. Congdon; Sten Anslan; Leho Tedersoo; Matt Field; Sandra E. Abell (Mycological Progress, 2021)
In recent decades, multipartite mutualisms involving microorganisms such as fungi have been discovered in associations traditionally thought of as bipartite. Ant-plant mutualisms were long thought to be bipartite despite fungi being noticed in an epiphytic ant-plant over 100 years ago. We sequenced fungal DNA from the three distinct domatium chambers of the epiphytic ant-plant Myrmecodia beccarii to establish if fungal communities differ by chamber type across five geographic locations spanning 675 km. The three chamber types serve different ant-associated functions including ‘waste’ chambers, where ant workers deposit waste; ‘nursery’ chambers, where the brood is kept; and ‘ventilation’ chambers, that allow air into the domatium. Overall, fungi from the order Chaetothyriales dominated the chambers in terms of the proportion of operational taxonomic units (OTUs; 13.4%) and sequence abundances of OTUs (28% of the total); however a large portion of OTUs (28%) were unidentified at the order level. Notably, the fungal community in the waste chambers differed consistently from the nursery and ventilation chambers across all five locations. We identified 13 fungal OTUs as ‘common’ in the waste chambers that were rare or in very low sequence abundance in the other two chambers. Fungal communities in the nursery and ventilation chambers overlapped more than either did with the waste chambers but were also distinct from each other. Differences in dominance of the common OTUs drove the observed patterns in the fungal communities for each of the chamber types. This suggests a multipartite mutualism involving fungi exists in this ant-plant and that the role of fungi differs among chamber types.

Spatial population genomics of a recent mosquito invasion - Thomas L. Schmidt; Tom Swan; Jessica Chung; Stephan Karl; Samuel Demok; Qiong Yang; Matt A Field; Mutizwa Odwell Muzari; Gerhard Ehlers; Mathew Brugh; Rodney Bellwood; Peter Horne; et al. (Molecular Ecology, 2021)
Population genomic approaches can characterize dispersal across a single generation through to many generations in the past, bridging the gap between individual movement and intergenerational gene flow. These approaches are particularly useful when investigating dispersal in recently altered systems, where they provide a way of inferring long‐distance dispersal between newly established populations and their interactions with existing populations. Human‐mediated biological invasions represent such altered systems which can be investigated with appropriate study designs and analyses. Here we apply temporally restricted sampling and a range of population genomic approaches to investigate dispersal in a 2004 invasion of Aedes albopictus (the Asian tiger mosquito) in the Torres Strait Islands (TSI) of Australia. We sampled mosquitoes from 13 TSI villages simultaneously and genotyped 373 mosquitoes at genome‐wide single nucleotide polymorphisms (SNPs): 331 from the TSI, 36 from Papua New Guinea (PNG) and four incursive mosquitoes detected in uninvaded regions. Within villages, spatial genetic structure varied substantially but overall displayed isolation by distance and a neighbourhood size of 232–577. Close kin dyads revealed recent movement between islands 31–203 km apart, and deep learning inferences showed incursive Ae. albopictus had travelled to uninvaded regions from both adjacent and nonadjacent islands. Private alleles and a co‐ancestry matrix indicated direct gene flow from PNG into nearby islands. Outlier analyses also detected four linked alleles introgressed from PNG, with the alleles surrounding 12 resistance‐associated cytochrome P450 genes. By treating dispersal as both an intergenerational process and a set of discrete events, we describe a highly interconnected invasive system.

Event-related and readiness potentials when preparing to approach and avoid alcohol cues following cue avoidance training in heavy drinkers - Lisa C. G. Di Lemma; Andrej Stancak; Vicente Soto; Nick Fallon; Matt Field (Psychopharmacology, 2020)
Rationale Cue avoidance training (CAT) reduces alcohol consumption in the laboratory. However, the neural mechanisms that underlie the effects of this intervention are poorly understood. Objectives The present study investigated the effects of a single session of CAT on event-related and readiness potentials during preparation of approach and avoidance movements to alcohol cues. Methods Heavy drinking young adults ( N = 60) were randomly assigned to complete either CAT or control training. After training, we recorded participants’ event-related and motor readiness potentials as they were preparing to respond. Results In the CAT group, N200 amplitude was higher when preparing to approach rather than avoid alcohol pictures. In the control group, N200 amplitudes did not differ for approach and avoidance to alcohol pictures. Regarding the late positive potential (LPP), in the CAT group, the negativity of this was blunted when preparing to avoid alcohol pictures relative to when preparing to avoid control pictures. In the control group, the negativity of the LPP was blunted when preparing to approach alcohol pictures relative to when preparing to approach control pictures. There were no effects on motor readiness potentials. Behavioural effects indicated short-lived effects of training on reaction times during the training block that did not persist when participants were given time to prepare their motor response before executing it during the EEG testing block. Conclusions After a single session of CAT, the enhanced N200 when approaching alcohol cues may indicate the engagement of executive control to overcome the associations learned during training. These findings clarify the neural mechanisms that may underlie the effects of CAT on drinking behaviour.

The effect of alcohol cue exposure and acute intoxication on inhibitory control processes and ad libitum alcohol consumption - Laura Baines; Matt Field; Paul Christiansen; Andrew Jones (Psychopharmacology, 2019)

Do daily fluctuations in inhibitory control predict alcohol consumption? An ecological momentary assessment study - Andrew Jones; Brian Tiplady; Katrijn Houben; Chantal Nederkoorn; Matt Field (Psychopharmacology, 2018)

Alcohol devaluation has dissociable effects on distinct components of alcohol behaviour - Abigail K Rose; Kyle Brown; James MacKillop; Matt Field; Lee Hogarth (Psychopharmacology, 2018)

Elevated alcohol consumption following alcohol cue exposure is partially mediated by reduced inhibitory control and increased craving - Matt Field; Andrew Jones (Psychopharmacology, 2017)

Cue avoidance training and inhibitory control training for the reduction of alcohol consumption: a comparison of effectiveness and investigation of their mechanisms of action - Lisa C. G. Di Lemma; Matt Field (Psychopharmacology, 2017)

Bibi ergo sum: the effects of a placebo and contextual alcohol cues on motivation to drink alcohol - Paul Christiansen; Gareth Townsend; Graeme Knibb; Matt Field (Psychopharmacology, 2017)

Acute stress increases ad-libitum alcohol consumption in heavy drinkers, but not through impaired inhibitory control - Elly McGrath; Andrew Jones; Matt Field (Psychopharmacology, 2016)

The ad-libitum alcohol ‘taste test’: secondary analyses of potential confounds and construct validity - Andrew Jones; Emily Button; Abigail K. Rose; Eric Robinson; Paul Christiansen; Lisa Di Lemma; Matt Field (Psychopharmacology, 2016)

Alcohol dependent patients have weak negative rather than strong positive implicit alcohol associations - Joanne M. Dickson; Claire Gately; Matt Field (Psychopharmacology, 2013)

Components of behavioural impulsivity and automatic cue approach predict unique variance in hazardous drinking - Paul Christiansen; Jon C. Cole; Andrew J. Goudie; Matt Field (Psychopharmacology, 2012)

Priming a restrained mental set reduces alcohol-seeking independently of mood - Andrew Jones; Jon Cole; Andrew Goudie; Matt Field (Psychopharmacology, 2011)

Effects of alcohol preload on attentional bias towards cocaine-related cues - Catharine Montgomery; Matt Field; Amanda M. Atkinson; Jon C. Cole; Andrew J. Goudie; Harry R. Sumnall (Psychopharmacology, 2010)

Effects of a low dose of alcohol on cognitive biases and craving in heavy drinkers - Tim Schoenmakers; Reinout W. Wiers; Matt Field (Psychopharmacology, 2008)

Biofilm formation in Desulfovibrio vulgaris Hildenborough is dependent upon protein filaments - Melinda E. Clark; Richard E. Edelmann; Matt L. Duley; Judy D. Wall; Matthew W. Fields (Environmental Microbiology, 2007)
Summary Desulfovibrio vulgaris Hildenborough is a Gram‐negative sulfate‐reducing bacterium (SRB), and the physiology of SRBs can impact many anaerobic environments including radionuclide waste sites, oil reservoirs and metal pipelines. In an attempt to understand D. vulgaris as a population that can adhere to surfaces, D. vulgaris cultures were grown in a defined medium and analysed for carbohydrate production, motility and biofilm formation. Desulfovibrio vulgaris wild‐type cells had increasing amounts of carbohydrate into stationary phase and approximately half of the carbohydrate remained internal. In comparison, a mutant that lacked the 200 kb megaplasmid, strain ΔMP, produced less carbohydrate and the majority of carbohydrate remained internal of the cell proper. To assess the possibility of carbohydrate re‐allocation, biofilm formation was investigated. Wild‐type cells produced approximately threefold more biofilm on glass slides compared with ΔMP; however, wild‐type biofilm did not contain significant levels of exopolysaccharide. In addition, stains specific for extracellular carbohydrate did not reveal polysaccharide material within the biofilm. Desulfovibrio vulgaris wild‐type biofilms contained long filaments as observed with scanning electron microscopy (SEM), and the biofilm‐deficient ΔMP strain was also deficient in motility. Biofilms grown directly on silica oxide transmission electron microscopy (TEM) grids did not contain significant levels of an exopolysaccharide matrix when viewed with TEM and SEM, and samples stained with ammonium molybdate also showed long filaments that resembled flagella. Biofilms subjected to protease treatments were degraded, and different proteases that were added at the time of inoculation inhibited biofilm formation. The data indicated that D. vulgaris did not produce an extensive exopolysaccharide matrix, used protein filaments to form biofilm between cells and silica oxide surfaces, and the filaments appeared to be flagella. It is likely that D. vulgaris used flagella for more than a means of locomotion to a surface, but also used flagella, or modified flagella, to establish and/or maintain biofilm structure.

Experimental manipulation of attentional biases in heavy drinkers: do the effects generalise? - Matt Field; Theodora Duka; Brian Eastwood; Robert Child; Mary Santarcangelo; Melanie Gayton (Psychopharmacology, 2007)

Do alcohol cues facilitate or impair cognitive processing in recently detoxified alcoholics? Commentary on Noel et al. (2007) - Matt Field; Jon Cole (Psychopharmacology, 2007)

Delay discounting and the behavioural economics of cigarette purchases in smokers: the effects of nicotine deprivation - Matt Field; Mary Santarcangelo; Harry Sumnall; Andrew Goudie; Jon Cole (Psychopharmacology, 2006)

Experimental manipulation of attentional bias increases the motivation to drink alcohol - Matt Field; Brian Eastwood (Psychopharmacology, 2005)

Attentional and approach biases for smoking cues in smokers: an investigation of competing theoretical views of addiction - Karin Mogg; Matt Field; Brendan P. Bradley (Psychopharmacology, 2005)

Alcohol increases cognitive biases for smoking cues in smokers - Matt Field; Karin Mogg; Brendan P. Bradley (Psychopharmacology, 2005)

Attentional biases for alcohol cues in heavy and light social drinkers: the roles of initial orienting and maintained attention - Matt Field; Karin Mogg; Jessica Zetteler; Brendan P. Bradley (Psychopharmacology, 2004)

Eye movements to smoking-related cues: effects of nicotine deprivation - Matt Field; Karin Mogg; Brendan P. Bradley (Psychopharmacology, 2004)